2014
DOI: 10.3390/polym6112862
|View full text |Cite
|
Sign up to set email alerts
|

Reversible-Deactivation Radical Polymerization of Methyl Methacrylate Induced by Photochemical Reduction of Various Copper Catalysts

Abstract: Photochemically mediated reversible-deactivation radical polymerization of methyl methacrylate was successfully performed using 50-400 ppm of various copper compounds such as CuSO4·5H2O, copper acetate, copper triflate and copper acetylacetonate as catalysts. The copper catalysts were reduced in situ by irradiation at wavelengths of 366-546 nm, without using any additional reducing agent. Bromopropionitrile was used as an initiator. The effects of various solvents and the concentration and structure of ligands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Very recently we showed that, regardless whether CuBr 2 or CuSO 4 .5H 2 O or various organic copper salts were used, the kinetic of polymerization of MMA was the same due to in situ formation of CuBr 2 by reaction of reduced copper compounds with an alkyl bromide initiator. 26 In the case of CuO, after its photochemical reduction, it can therefore be expected that the polymerization will be controlled by an in situ formed CuBr/CuBr 2 equilibrium. Logically, the molar mass and dispersity of the polymers are slightly higher for the CuO in comparison with polymerization started with CuBr 2 because in the first case there is no CuBr 2 deactivator present in the polymerization mixture in the first stage of polymerization.…”
Section: Tolerance Of Photordrp Of Mma To Presence Of Oxygenmentioning
confidence: 99%
“…Very recently we showed that, regardless whether CuBr 2 or CuSO 4 .5H 2 O or various organic copper salts were used, the kinetic of polymerization of MMA was the same due to in situ formation of CuBr 2 by reaction of reduced copper compounds with an alkyl bromide initiator. 26 In the case of CuO, after its photochemical reduction, it can therefore be expected that the polymerization will be controlled by an in situ formed CuBr/CuBr 2 equilibrium. Logically, the molar mass and dispersity of the polymers are slightly higher for the CuO in comparison with polymerization started with CuBr 2 because in the first case there is no CuBr 2 deactivator present in the polymerization mixture in the first stage of polymerization.…”
Section: Tolerance Of Photordrp Of Mma To Presence Of Oxygenmentioning
confidence: 99%
“…In the initial stages of photodegradation, randomly distributed weak bonds can be broken quickly [37]. The degree of deterioration (α) was calculated by the use of Equation (10).…”
Section: = /mentioning
confidence: 99%
“…A number of UV-stabilizers are known in which the mode of action is highly dependent on the direct UV absorption, radical scavengers, peroxide decomposers, excited state quenchers and light screeners, for example [6][7][8][9][10][11][12][13][14][15]. Recently, we have reported the use of various additives to increase photostabilizing efficiency and photochemical stability of polymeric materials [16][17][18][19] as part of our interest in the synthesis of polymeric materials with interesting applications [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The photostabilization of polymers has to be considered, which involves the retardation of photochemical reactions in polymeric materials that occur during the irradiation process. Various stabilizing systems have been developed that depend on the stabilizer action, such as excited state quenchers, light screeners, peroxide decomposers, radical scavengers, UV absorbers and luminescent shifters [6][7][8][9][10][11][12][13][14]. As part of our on-going research on the synthesis of polymeric materials [15][16][17][18] and polymer stabilization [19,20], we became interested in the photostabilization of PMMA using 2-(6-methoxynaphthalen-2-yl)propanoate with Sn(II), Ni(II), Zn(II) and Cu(II) complexes.…”
Section: Introductionmentioning
confidence: 99%